Estudio de prefactibilidad para la instalación de una planta procesadora y comercializadora de pellets compostables a base de arroz y bagazo de caña de azúcar, destinados a la industria plástica del Perú - Cerrate Poves, Karla Karen (2020)
When evaluating the present proposal with an investment of 5.353MM Soles and an OCC of 14.47%, a Financial NPV of 6.163MM Soles, a Financial IRR of 38% and a recovery period of 3.68 years have been obtained, demonstrating the project to be profitable. Currently, the Peruvian plastic industry does not have a developed petrochemical industry that goes hand in hand with its production requirements. Likewise, as the Plastics Law was approved in 2018, the change in legislation presents an opportunity to satisfy the need of companies that produce single-use plastics, which in the new legal context require alternative ecological raw materials in order to continue their operation. The purpose of this research is then to demonstrate the commercial, technical, economic, financial and social viability at the pre-feasibility study level for the installation of a production and marketing plant for compostable pellets. The proposal intends to use national resources and take advantage of the vast availability of agricultural waste, thus generating a positive impact throughout the production chain. It was determined that there is a potential market for the product´s industrial use, with the project's demand for the first and last year being of 443.78 and 519.47 tons respectively. The production plant will be located in the Huachipa district, belonging to the Lima Metropolitan province and will have a production capacity of 648.3 tons. Regarding the selection of existing technology for the production process, there are no limitations, since all the equipment can be found for sale in the market. In the same way, technical standards and HACCP have been considered for the required control measures. Finally, the proposal also has a positive impact on the project's area of influence, measured through added value, since to generate S / .1 of added value, S / .0.50 must be invested.